Medieval Latin Aristotle Commentaries Supplementary Authors - Lohr, Charles H. (Traditio, 1974)
To the inventory of Medieval Latin Aristotle Commentaries published in Traditio 23 (1967) 313-413, 24 (1968) 149-245, 26 (1970) 135-216, 27 (1971) 251-351, 28 (1972) 281-396, and 29 (1973) 93-197, I would like to make the following additions and corrections. They consist of a list of additional authors with biobibliographical note and indication of manuscripts and editions.